The teaching of Philippine nationalism in the public elementary schools in the City of Manila - Descalzo, Cecilia Bautista (Mariano) 1909- (1955)
The contents of eighteen textbooks, consisting of twelve basic readers and six social studies textbooks in the public elementary schools in the City of Manila were examined and analyzed quantitatively and qualitatively to answer the problems stated in this study. These problems include determining the nationalistic contents of the basic readers and social studies textbooks that may develop Philippine Nationalism in the public elementary school, determining the methods used in teaching nationalism, and determining the measures adapted by the public elementary schools to improve the teaching of Philippine Nationalism.